PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI ULANG LIPSTIK MEREK WARDAH PADA MAHASISWI UNIVERSITAS TADULAKO PALU - MULYANI, MULYANI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2015)
This research iams to know the effect of Product Quality to interest of repurchasing wardah lipstick of economics faculty students of tadulako university. The research method used in this research is descriptive causal.. The population in this research is student female use Brand Wardah Lipstick at Tadulako University of Palu. Sampling technique using Snowball, with the samples of 60 respondents. Data collection using questionnaires. The method of analysis using multiple linear regression. The results indicate that product quality variables significantly influence the interest in buying back Lipstick Wardah brand on student Tadulako University Palu.